2020
DOI: 10.9734/ajr2p/2020/v3i430126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group Work in Addressing the Misconceptions of Light

Abstract: Physics is science that determines the living and life styles of the people. However, it has many misconceptions in the concepts. In this study, the effect of group work and traditional method in addressing the Class IX student’s misconceptions about light is investigated. The explanatory sequential mixed method was used for the study. It was carried out in one of the Middle Secondary School [MSS] under Trashigang district. The sample of this study consisted of 42 Class IX students and 5 science teachers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The activities presented in this study can be used in teaching optics topics and to eliminate the misconceptions such as 'the colour of light does not affect the refractive index of the medium' [27]. In addition, it is thought that RayLab can be used in teaching topics in geometric optics other than dispersion, as Snell's Law, lenses, refractive mediums, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The activities presented in this study can be used in teaching optics topics and to eliminate the misconceptions such as 'the colour of light does not affect the refractive index of the medium' [27]. In addition, it is thought that RayLab can be used in teaching topics in geometric optics other than dispersion, as Snell's Law, lenses, refractive mediums, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Visualization of the movement of sound particles also increases, so students will easily understand and develop more meaningful concepts. The results of physics research in Bhutan revealed that the average score of students' physics misconceptions was 52.60 [44]. It is because students find it difficult to explain an abstract phenomenon.…”
Section: S4mentioning
confidence: 99%